Wawasan Alqur’an Dan Hadis Tentang Harta Dan Kepemilikan - Wahyuni, Firma Lovi (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2019)
Al-Quran Insight and Hadith about Property and Ownership. Property is anything that pleases humans and they maintain, both in material form and in the form of benefits. Islam regulates the problem of property and its exchange, namely matters relating to exchange of assets, including the sale and purchase (ba'i), rent (ijarah), debt, and other matters related to muamalat. In Islam assets have a high value. Assets are only a mandate that must be maintained in order to bring good in the world and at the same time salvation and happiness in the hereafter. Property ownership is a relationship between humans and assets determined by syara in the form of special treatment of the property, which makes it possible to use it in general until there is a prohibition on using it.